Admission Brain Cortical Volume: An Independent Determinant of Poststroke Cognitive Vulnerability. Issue 8 (August 2017) - Sagnier, Sharmila; Catheline, Gwenaëlle; Dilharreguy, Bixente; Munsch, Fanny; Bigourdan, Antoine; Poli, Mathilde; Debruxelles, Sabrina; Olindo, Stéphane; Renou, Pauline; Rouanet, François; Dousset, Vincent; Tourdias, Thomas; et al.
Abstract : Background and Purpose—: Several markers of poststroke cognitive impairment have been reported. The role of brain cortical volume remains uncertain. The aim of this study was to evaluate the influence of brain cortical volume on cognitive outcomes using a voxel-based morphometry approach in subjects without prestroke dementia. Methods—: Ischemic stroke patients were prospectively recruited 24 to 72 hours post stroke (M0). Cognition was evaluated at M0, 3 months, and 1 year (M12) using the Montreal Cognitive Assessment, the Isaacs set test, and the Zazzo's cancellation task. A 3-T brain magnetic resonance imaging was performed at M0. Grey matter (GM) was segmented using Statistical Parametric Mapping 12 software. Association between global GM volume and cognitive score slopes between M0 and M12 was evaluated using a linear mixed model. Correlations between focal GM volumes and changes in cognitive performance were evaluated using Statistical Parametric Mapping 12. Results—: Two-hundred forty-eight patients were included (mean age 65±SD 14 years old, 66% men). Global GM volume was significantly associated with changes in Montreal Cognitive Assessment scores (β=0.01; P =0.04) and in the number of errors on the Zazzo's cancellation task (β=−0.02; P =0.04) independently of other clinical/radiological confounders. Subjects with lower GM volumes in the left fronto-temporo-insular cortex were more vulnerable to transient Montreal Cognitive Assessment and Isaacs set test impairment. Subjects with lower GM volumes in right temporo-insular cortex, together with basal ganglia, were more vulnerable to transient cognitive impairment on the Zazzo's cancellation task. Conclusions—: Smaller cortical volumes in fronto-temporo-insular areas measured 24 to 72 hours post stroke are associated with cognitive vulnerability in the subacute stroke phase. Abstract : Supplemental Digital Content is available in the text.